Literasi Keuangan Pada Karyawan Yang Bekerja Pada Jasa Keuangan Di DKI Jakarta - Farah Margaretha, Reza Arief Pambudhi (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2014)
This study aims to examine the influence of financial literacy, personal financial attitude, gender, age, education level and martial status toward the forms of personal debt on the employees who works in financial services in DKI Jakarta.